Knowledge, Attitude and Practices of Antimicrobial Use among Veterinarians and Para-Veterinarians in Gaza Strip, Palestine - A Elmanama, Abdelraouf; ES Abu Tayyem, Noor; S Winkler, Mirko; I. Abu-Dan, Renad; W. El Hindi, Mahmoud (The Iraqi Journal of Veterinary Medicine, 2025)
Antimicrobial resistance (AMR) is an emerging global public health problem. Rationale use of antimicrobials can prevent the rise of this problem. The objective of this study is to characterize the knowledge, attitudes, and practices of antibiotic usage and AMR among veterinarians and para-veterinarians in Gaza Strip, Palestine. A cross-sectional study was conducted through the collection of a questionnaire from 86 personnel who served as part of a veterinary aid system, in September_ October 2022. The results show that the most common infections treated are respiratory tract infections (18%), mastitis (17%), and diarrhea (17%). The most frequent antibiotics used were penicillin/strepto-penicillin (15.6%), tetracycline/oxytetracycline (15.3%), and erythromycin (5.1%). About one-third (29.6%) of respondents relied on their previous experience when prescribing antibacterial. Nine in ten (90.7%) believed that there is ongoing antibacterial abuse in the veterinarian sector, and two-thirds (63.5%) believed that the use of wide-spectrum antibacterial is better than the narrow spectrum. The large majority of participants (91.9%) considered AMR a serious public health threat. Although most veterinarians and para-veterinarians in Gaza Strip consider the AMR a serious problem, many of them are contributing to the antimicrobial abuse in the veterinary sector. Targeted educational programs on responsible antimicrobial use and AMR are highly recommended for workers in the veterinary field. This should be implemented by regulating and monitoring the use of antimicrobials among veterinarians as well as farmers‎‎‎.